The Effect of Using Smart Diabetes Calendar (SDC) on the Self-Efficacy of Diabetes Mellitus Patients - Tantri Widyarti Utami; Yunani Sri Astuti; Nurhalimah Nurhalimah; Yasmin Kusumaningtyas (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes mellitus is one of the fastest growing health emergencies worldwide in the 21st century and has the second largest negative impact on life expectancy. Diabetes management, such as increasing knowledge about the disease, treatment, and lifestyle modifications, is an efficient and effective way to manage the disease. Self-efficacy is the cultivation of patients' confidence in managing their disease so that their quality of life improves. Objective to determine the effect of using the Smart Diabetes Calendar (SDC) on the self-efficacy of patients with diabetes mellitus Method, The design used was a “quasi-experimental pre-post test with control group” with the intervention of a smart diabetes calendar (SDC). The sampling technique used was purposive sampling. Researchers selected respondents based on inclusion criteria and research objectives The inclusion criteria for this study were type 2 diabetes patients, aged 35-75 years, taking anti-diabetic drugs, not undergoing treatment in a hospital, and able to read and write. The research instrument used the General Self-Efficacy (GSE) scale. The sample size was 93 respondents. Data analysis used independent t-tests and paired t-tests. The results of this study showed an increase in the self-efficacy of DM patients after using SDC (p-value=0.000). The conclusion of this study is that the use of a smart diabetes calendar (SDC) increases the self-efficacy of diabetes mellitus patients. DM patients also increased their compliance and discipline in managing their disease.